Bone Marrow Mesenchymal Stem Cell-Derived Exosomal MicroRNA-126-3p Inhibits Pancreatic Cancer Development by Targeting ADAM9 - Dong-Mei Wu; Xin Wen; Xin-Rui Han; Shan Wang; Yong-Jian Wang; Min Shen; Shao-Hua Fan; Zi-Feng Zhang; Qun Shan; Meng-Qiu Li; Bin Hu; Jun Lu; et al. (Elsevier, 2019)
Pancreatic cancer is a lethal malignancy with relatively few effective therapies. Recent investigations have highlighted the role of microRNAs (miRNAs) as crucial regulators in various tumor processes including tumor progression. Hence the current study aimed to investigate the role of bone marrow mesenchymal stem cell (BMSC)-derived exosomal microRNA-126-3p (miR-126-3p) in pancreatic cancer. Initially, miRNA candidates and related genes associated with pancreatic cancer were screened. PANC-1 cells were transfected with miR-126-3p or silenced a disintegrin and a metalloproteinase-9 (ADAM9) to examine their regulatory roles in pancreatic cancer cells. Additionally, exosomes derived from BMSCs were isolated and co-cultured with pancreatic cancer cells to elucidate the effects of exosomes in pancreatic cancer. Furthermore, the effects of overexpressed miR-126-3p derived from BMSCs exosomes on proliferation, migration, invasion, apoptosis, tumor growth, and metastasis of pancreatic cancer cells were analyzed in connection with lentiviral packaged miR-126-3p in vivo. Restored miR-126-3p was observed to suppress pancreatic cancer through downregulating ADAM9. Notably, overexpressed miR-126-3p derived from BMSCs exosomes inhibited the proliferation, invasion, and metastasis of pancreatic cancer cells, and promoted their apoptosis both in vitro and in vivo. Taken together, the key findings of the study indicated that overexpressed miR-126-3p derived from BMSCs exosomes inhibited the development of pancreatic cancer through the downregulation of ADAM9, highlighting the potential of miR-126-3p as a novel biomarker for pancreatic cancer treatment. Keywords: bone marrow mesenchymal stem cells, exosomes, microRNA-126-3p, a disintegrin and a metalloproteinase-9, pancreatic cancer, invasion, metastasis